The hidden diversity and inland radiation of Sri Lanka's ground-dwelling geckos of the genus Cyrtodactylus (Reptilia: Gekkonidae). Issue 1 (31st December 2022) - Amarasinghe, A. A. Thasun; Karunarathna, Suranjan; Campbell, Patrick D.; Gayan, A. K. Anusha; Ranasinghe, W. D. Bhanuka; De Silva, Anslem; Mirza, Zeeshan A.
Abstract : The genus Cyrtodactylus has recently been classified phylogenetically into several clades, subclades, groups, and some into Sri Lankan Cyrtodactylus . Certain complexes from the Indian subcontinent have been assigned to the " C . triedrus group". This group is comprised of medium-sized species (SVL 50.6–105.7 mm) and are composed of five major species complexes: fraenatus, triedrus, deccanensis, jeyporensis, and collegalensis . Among these complexes, the latter four are composed of ground and litter dwelling species, which were previously assigned to the genus Geckoella ; and is currently being treated as a subgenus. Cyrtodactylus triedrus, an endemic species of Sri Lanka, has long been considered a widely distributed single species in this part of the world. Based on morphological and phylogenetic evidences, we demonstrate that C . ( G .) triedrus is not a single species, but a species complex. We also describe a new species that is restricted to intermediate savanna-mixed dry lowland forested habitats. Furthermore, we resurrect Geckoella punctata, assign it to the genus Cyrtodactylus and designate a lectotype that we redescribe. The genetic divergence across species of the C . triedrus clade varies between 11–26% in the studied fragment of the mitochondrial NADH dehydrogenase subunit 2 gene. The molecular phylogeny of the ground dwelling radiation of the subgenus Geckoella indicates deep splits between the Indian species and Sri Lankan endemic C . ( G .) triedrus sensu stricto, and between Indian dry and wet zone clades. Cyrtodactylus ( G .). triedrus is restricted to the moist or submontane forests in the Central highlands of Sri Lanka and is redescribed herein based on its holotype. http://zoobank.org/urn:lsid:zoobank:org:pub:3B37037C-EE9F-4011-BEC9-47E1F3BB6779